Pendidikan Islam dalam Pengembangan Potensi Manusia - M. Slamet Yahya (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Human is subject as well as object of education. As subject human determine education’s type and direction, and as subject he became focus of entire education activities. Therefore, every formulation of education has to refer to human on every dimension, which are reflection of dynamic thought or empirical reality. Without human orientation, that formulation can’t anticipate change, and education’s practice will fail. Human is a creature with two elements, namely material (jasmani) and immaterial (ruhani), and equipped with fitrah, nafs, qalb, ruh, and aql. With those instruments, human have potential, positive and negative. Positive potential have to be developed optimally and negative potential must be minimized, and education is appropriate means to build and develop good potentials.